Synthetic Polymer as an Adjuvant in Collagen‐Induced Arthritis. Issue 1 (21st March 2014) - Shakya, Akhilesh Kumar; Nandakumar, Kutty Selva
Abstract: Collagen‐induced arthritis (CIA), the classical animal model for experimental arthritis, resembles human rheumatoid arthritis in several aspects. However, the most widely used method of inducing CIA utilizes Freund's adjuvants, which can skew the elicited immune responses and also pose toxicity problems. This unit describes a new method of inducing CIA using a well defined stimuli‐responsive synthetic polymer, poly‐ N ‐isopropylacrylamide‐based adjuvant, mixed with the joint cartilage protein collagen type II (CII). PNiPAAm as an adjuvant is biodegradable and biocompatible, and does not skew immune responses. Thus, it is helpful in the development of arthritis models for studying antigen and tissue ‐specific autoimmune responses in an unbiased manner. This model is valuable for analyzing disease pathways, positional identification of genes regulating arthritis, validation of existing therapies, and exploring new therapeutic targets. Furthermore, this newly developed PNiPAAm adjuvant allows investigation of disease induction using specific autoantigens in several autoimmune diseases independently of toll‐like receptors, as well as optimization of vaccine delivery systems for infectious diseases. Curr. Protoc. Mouse Biol . 4:11‐24 © 2014 by John Wiley & Sons, Inc.